Perspektif Hadis Arah Kiblat Tanah Haram - Fatmawati, Emyllia (AL - AFAQ : Jurnal Ilmu Falak dan Astronomi, 2021)
Muslim face their own Qibla compilations. The direction of the accurate Qibla is very difficult to predict, compiling to make a mosque or going to pray facing the Qibla requires more caution because straying a few degrees will change the position of kilometers from Kaaba. Qibla issues that do not exist are problems with Qibla Direction in Mecca (Jiyatul Ka'bah). The location is very far from the Kaaba and cannot be accessed directly here. The direction of kibla has been discussed in the Quran and the Hadith, Imam Syafi'i who is considered a Muslim, is required to face the Ainul Kaaba, and if the prayer is not right the the other scholars who apprear Syafi'i said that the compilation can be used see Ka'bah the can face the Jiyah Kaaba.